2017
DOI: 10.3892/ol.2017.6883
|View full text |Cite
|
Sign up to set email alerts
|

Blocking integrin β1 decreases adhesion in chemoresistant urothelial cancer cell lines

Abstract: Abstract. Treatment failure in metastatic bladder cancer is commonly caused by acquisition of resistance to chemotherapy in association with tumor progression. Since alterations of integrins can influence the adhesive and invasive behaviors of urothelial bladder cancer cell lines, the present study aimed to evaluate the role of integrins in bladder cancer cells with acquired resistance to standard first-line chemotherapy with gemcitabine, and cisplatin. Therefore, four gemcitabineand four cisplatin-resistant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Additionally, we confirmed impact of selected CAMs on single B-cell adhesion in optical tweezers by using of function-blocking antibodies to β integrins and cadherin-2 on representative cell lines and primary B-cells. We observed that the formation of adhesion between B-cell and MSC prolonged significantly when β1 integrin and cadherin-2 were blocked with appropriate antibody what is in line with literature [ 61 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we confirmed impact of selected CAMs on single B-cell adhesion in optical tweezers by using of function-blocking antibodies to β integrins and cadherin-2 on representative cell lines and primary B-cells. We observed that the formation of adhesion between B-cell and MSC prolonged significantly when β1 integrin and cadherin-2 were blocked with appropriate antibody what is in line with literature [ 61 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…The integrin β subunit has been characterized as a therapeutic target due to its abundance in high-grade bladder cancer cells and correlation with mitomycin resistance (Zhang et al, 2012). The application of integrin β1 antibody was shown to attenuate adhesive and invasive behaviors in drug-resistant urothelial cancer cell lines (Vallo et al, 2017). In addition, integrin signal transduction was found to recruit FAK and paxillin, which are required for intracellular integrin signal transduction (López-Colomé et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This also reveals the concordance of our previous findings where we identified the activation of integrin signaling in the non-type bladder carcinoma. Targeting integrins have shown to decrease angiogenesis, tumor growth and metastasis in other cancers including bladder carcinoma [36,37,38]. FAK activation has also been reported to regulate bladder cancer invasion and migration which also makes it a favorable therapeutic target for bladder carcinoma [39].…”
Section: Discussionmentioning
confidence: 99%